Numerical simulation of non-steady flows around solid bodies with arbitrary motion using a weakly-compressible Smoothed Particle Hydrodynamics method. - García Pérez, Alejandro (My University, 2018)
Meshless, SPH, Buoyancy.
Keywords: Meshless, SPH, Buoyancy.